Pd- and Photo-Promoted C−H Functionalizations of Phospholes - Xu, Shibo; Hirano, Koji (Synlett, 2025)
Significant research efforts have been devoted to the synthesis of substituted phospholes due to their exceptional optical and physical properties. In contrast to conventional methods, the direct C−H functionalizations of readily accessible phospholes offer an efficient and modular route to structurally diverse phosphole derivatives. In this account, we present our research group’s advancements in the regioselective C−H functionalizations of benzophospholes, including: (1) palladium-catalyzed C−H arylation, alkenylation, and alkynylation; (2) organophotoredox-catalyzed C−H alkoxycarbonylation, phosphinylation, and alkylation; and (3) related photo-promoted dehydrogenative cyclization and palladium-catalyzed annulative π-extension.
Keywords: Annulation; Benzophosphole; C−H functionalization; Heterocycles; Organophotocatalysis; Mallory reaction; Palladium catalysis